Social innovation in health: strengthening Community Systems for Universal Health Coverage in rural areas - Lindi van Niekerk; Martha Milena Bautista-Gomez; Barwani Khaura Msiska; Jana Deborah B. Mier-Alpaño; Arturo M. Ongkeko; Lenore Manderson (BMC, 2023)
Abstract Background In seeking the attainment of Universal Health Coverage (UHC), there has been a renewed emphasis on the role of communities. This article focuses on social innovation and whether this concept holds promise to enhance equity in health services to achieve UHC and serve as a process to enhance community engagement, participation, and agency. Methods A cross-country case study methodology was adopted to analyze three social innovations in health in three low- and middle-income countries (LMICs): Philippines, Malawi, and Colombia. Qualitative methods were used in data collection, and a cross-case analysis was conducted with the aid of a simplified version of the conceptual framework on social innovation as proposed by Cajaiba-Santana. This framework proposes four dimensions of social innovation as a process at different levels of action: the actors responsible for the idea, the new idea, the role of the institutional environment, and the resultant changes in the health and social system. Results The study found that each of the three social innovation case studies was based on developing community capacities to achieve health through community co-learning, leadership, and accountability. The process was dependent on catalytic agents, creating a space for innovation within the institutional context. In so doing, these agents challenged the prevailing power dynamics by providing the communities with respect and the opportunity to participate equally in creating and implementing programs. In this way, communities were empowered; they were not simply participants but became active agents in conceptualizing, implementing, monitoring, and sustaining the social innovation initiatives. Conclusion The study has illustrated how three creative social innovation approaches improved access and quality of health services for vulnerable rural populations and increased agency among the intervention communities. The processes facilitated empowerment, which in turn supported the sustained strengthening of the community system and the achievement of community goals in the domain of health and beyond.